2022
DOI: 10.3390/foods11030439
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Sunflower Oil with Ultrasound-Assisted Extracted Bioactive Compounds from Crithmum maritimum L.

Abstract: Crithmum maritimum L., or sea fennel, is an edible halophyte plant, rich in phenolic compounds with antioxidant and antimicrobial activities, that naturally grows in Mediterranean coasts. This study aims to incorporate bioactive compounds extracted from lyophilized Crithmum maritimum to sunflower oil assisted by ultrasounds (UAE), to improve its biological value and oxidative stability. UAE conditions were optimized as a function of time (5–20 min) and lyophilized plant concentration (5–20% m/v). The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
3
13
1
Order By: Relevance
“…Specifically, the genotype G4 In the same way, DPPH ranged from 2.24 to 14.92 mg of TE/g dw in different genotypes of C. maritimum, exhibiting the following descending order: G14 > the majority of genotypes > G13 and G16 (Figure 1b). Generally, DPPH values in native Greek genotypes of C. maritimum presented an average value of 8.0 mg of TE/g dw, which is in accordance with those of Sousa et al [30], who found a value of 7.3 mg of TE/g dw. Previous studies in the literature presented a DPPH scavenging activity of C. maritimum, expressed as IC 50 , of around 7.6 mg/mL [29], or ranged from 0.15 to 1.21 mg/mL [14].…”
Section: Determined By Lc-mssupporting
confidence: 89%
“…Specifically, the genotype G4 In the same way, DPPH ranged from 2.24 to 14.92 mg of TE/g dw in different genotypes of C. maritimum, exhibiting the following descending order: G14 > the majority of genotypes > G13 and G16 (Figure 1b). Generally, DPPH values in native Greek genotypes of C. maritimum presented an average value of 8.0 mg of TE/g dw, which is in accordance with those of Sousa et al [30], who found a value of 7.3 mg of TE/g dw. Previous studies in the literature presented a DPPH scavenging activity of C. maritimum, expressed as IC 50 , of around 7.6 mg/mL [29], or ranged from 0.15 to 1.21 mg/mL [14].…”
Section: Determined By Lc-mssupporting
confidence: 89%
“…The results showed that there was a significant difference at the probability level (0.05 < P) between time (0) and the other times (5,10,15), and also significant differences were recorded at the probability level (0.05 < P) among times (5,10,15). This is in agreement with the findings of [26], in an experiment conducted on sunflower oil and supplementing it with bioactive compounds extracted with the ultrasonic weaves .The reason for the low acidity may due to the exposure time to ultrasound, as well as the oil concentration, which have a positive effect on the acidity value, and this disagree with [27], in an experiment conducted on peanut oil with the ultrasonic waves at different frequencies, where it was noted that the value of acidity at the frequency of 20 kHz was (0.16), which was slightly higher than those that do not use ultrasound treatment. The reason for this is due to the frequency less than 40 kHz, in which the cavity intensity becomes weaker with the increase in frequency, thus the acidity value increases while in the frequency more than 40 kHz, the cavity intensity becomes stronger with the increase in frequency, and thus the acidity value decreases.…”
Section: Acidity Numbersupporting
confidence: 94%
“…Crithmum maritimum L. (Apiaceae), known as sea fennel or rock samphire, is a facultative halophyte widely distributed in coastal habitats throughout Western Europe that is well-known for a variety of food and other uses (Renna, 2018). Its leaves display high antioxidant and nutritional value (Nabet et al, 2017;Sánchez-Faure et al, 2020), and its seeds contain appreciable amounts of good-quality, edible oil and secondary metabolites with different potential industrial applications (Pavela et al, 2017;Martins-Noguerol et al, 2022a;Sousa et al, 2022). Apart from its nutritional value, C. maritimum could be a viable alternative crop in nutrientpoor or degraded soils that are not suitable for conventional species (Karkanis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%